Green Human Reosurce Management : A Bibiometric Analysis - Avrelia Refi Chantika; Masiyah Kholmi (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Green Human Resource Management (GHRM) is a human resource management approach that is increasingly important in the context of organizational sustainability. Bibliometric studies highlight trends, patterns, and developments in GHRM research to provide insight into the contribution and evolution of this concept. This paper presents a bibliometric review of the GHRM literature, exploring research focus, methods used, and directions of development. Bibliometric analysis can help identify research gaps and provide a foundation for the development of more sustainable GHRM theory and practice in the future.